2020
DOI: 10.31234/osf.io/p6e9c
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An excess of positive results: Comparing the standard Psychology literature with Registered Reports

Abstract: When studies with positive results that support the tested hypotheses have a higher probability of being published than studies with negative results, the literature will give a distorted view of the evidence for scientific claims. Psychological scientists have been concerned about the degree of distortion in their literature due to publication bias and inflated Type-1 error rates. Registered Reports were developed with the goal to minimise such biases: In this new publication format, peer review and the decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
138
2
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(146 citation statements)
references
References 33 publications
3
138
2
3
Order By: Relevance
“…We found that 62% of claims made in our sample of animal physical cognition papers were positive, 22% were negative and 16% were inconclusive. This figure of 62% positive claims is lower than previous reports of ~90% positive claims in psychology in general (Fanelli, 2010), and closer to the ~50% of positive findings from novel Registered Report studies in psychology (Scheel et al, 2020). This suggests that animal physical cognition research in general may not have an intense bias towards positive claims and positive results, and that animal physical cognition research is receptive to negative reports.…”
Section: Discussionsupporting
(Expert classified)
“…We found that 62% of claims made in our sample of animal physical cognition papers were positive, 22% were negative and 16% were inconclusive. This figure of 62% positive claims is lower than previous reports of ~90% positive claims in psychology in general (Fanelli, 2010), and closer to the ~50% of positive findings from novel Registered Report studies in psychology (Scheel et al, 2020). This suggests that animal physical cognition research in general may not have an intense bias towards positive claims and positive results, and that animal physical cognition research is receptive to negative reports.…”
Section: Discussionsupporting
(Expert classified)
“…[Insert Figure 6 here] Lack of standardisation. Previous analyses by Hardwicke et al 82 and Scheel et al 56 show that RRs are registered and reported inconsistently and, in many cases, even lack sufficient information to determine the specific hypotheses. This lack of specificity likely arises from the incompatibility between the 17 th -century traditional manuscript format -involving discursive and often vague prose documentationand the demand for quasi-mathematical precision within RRs.…”
Section: Limitation and Drawbacksmentioning
confidence: 98%
“…We note that adopting such methods is challenging: they involve additional costs such as more time in the preparation phase of the study and less flexibility (Allen and Mehler, 2019). However, recent preliminary meta-research suggests that the chances of publishing findings that do not meet traditional statistical thresholds increases remarkably for studies published as Registered Reports (Allen and Mehler, 2019;Scheel et al, 2020) while citation counts are comparable to traditional papers (Hummer et al, 2019). Hence, increased transparency not only benefits the field, but likely also individual authors.…”
Section: The Potential Of Fnirs For Neurofeedback Research -Future DImentioning
confidence: 99%